Effects of Upper Arm and Breathing Exercise on Interleukin-6 in COVID-19 Patients - Tarigan, Amira Permatasari; Listyoko, Aditya Sri; Pandia, Pandiaman; Pradana, Andika; Eyanoer, Putri Chairani; Sinaga, Sudirman Parningotan; Vera, Yeni; Firdaus, Ruby; Ramadhani, Adini Arifah (Faculty of Medicine Universitas Airlangga, 2024)
Introduction: COVID-19 disease has become a comprehensive world issue and has been declared a significant threat to global health. Interleukin-6 (IL-6) is an important inflammatory marker and one of the triggers of the cytokine storm in COVID-19, where increased levels can be an independent predictor of COVID-19 mortality. This study aimed to observe the effect of upper arm and breathing exercises on IL-6 levels in severe COVID-19 patients. Methods: The study design was quasi-experimental, with blood tests conducted before and after the examination. A total of 20 patients with confirmed COVID-19 were involved, divided into intervention and control groups. Results: Blood tests to determine baseline IL-6 levels were performed in all patients. Patients from the intervention group were given upper arm and breathing exercises for ten days, twice a day, via video tutorials on mobile phones, while patients from the control group did not receive any exercises. Patients from the intervention group obtained mean pre- and post-exercise IL-6 levels of 42.38 ± 48.48 and 16.78 ± 18.29, respectively (p = 0.005). Conclusion: Upper arm and breathing exercises showed significant changes in IL-6 levels in severe COVID-19 patients.